Analysis of carbon-binder domain morphology and correlation to effective ion transport properties - Mrudula Prasad; Benedikt Prifling; Matthias Neumann; Simon Hein; Rares Scurtu; Alice Hoffmann; André Hilger; Markus Osenberg; Ingo Manke; Margret Wohlfahrt-Mehrens; Volker Schmidt; Arnulf Latz; et al. (Journal of Power Sources Advances)
The conductive additive and binder domain (CBD) is an essential component of lithium-ion battery electrodes. It enhances the electrical connectivity and mechanical stability within the solid electrode matrix. The CBD aggregate exhibits inner porosity that significantly impacts ion transport within the electrode. Thus, the spatial distribution of CBD and its morphology play a critical role for ion transport pathways within the electrode. In order to quantify the extent of this influence, we employ high-resolution focused ion beam/scanning electron microscopy (FIB-SEM) imaging and isolate regions with just solid CBD and pore. This enables us to quantitatively correlate the CBD morphology with physical transport parameters and present a function that describes the relationship between CBD porosity and its ionic conductivity. Through our work, we provide insights into the CBD microstructure for use in future continuum-scale models.